Evidence-based practice in neonatal health: knowledge among primary health care staff in northern Viet Nam - Persson Lars-Åke; Målqvist Mats; Nga Nguyen; Eriksson Leif; Ewald Uwe; Wallin Lars (BMC, 2009)
Abstract Background An estimated four million deaths occur each year among children in the neonatal period. Current evidence-based interventions could prevent a large proportion of these deaths. However, health care workers involved in neonatal care need to have knowledge regarding such practices before being able to put them into action. The aim of this survey was to assess the knowledge of primary health care practitioners regarding basic, evidence-based procedures in neonatal care in a Vietnamese province. A further aim was to investigate whether differences in level of knowledge were linked to certain characteristics of community health centres, such as access to national guidelines in reproductive health care, number of assisted deliveries and geographical location. Methods This cross-sectional survey was completed within a baseline study preparing for an intervention study on knowledge translation (Implementing knowledge into practice for improved neonatal survival: a community-based trial in Quang Ninh province, Viet Nam, the NeoKIP project, ISRCTN44599712). Sixteen multiple-choice questions from five basic areas of evidence-based practice in neonatal care were distributed to 155 community health centres in 12 districts in a Vietnamese province, reaching 412 primary health care workers. Results All health care workers approached for the survey responded. Overall, they achieved 60% of the maximum score of the questionnaire. Staff level of knowledge on evidence-based practice was linked to the geographical location of the CHC, but not to access to the national guidelines or the number of deliveries at the community level. Two separated geographical areas were identified with differences in staff level of knowledge and concurrent differences in neonatal survival, antenatal care and postnatal home visits. Conclusion We have identified a complex pattern of associations between knowledge, geography, demographic factors and neonatal outcomes. Primary health care staff knowledge regarding neonatal health is scarce. This is a factor that is possible to influence and should be considered in future efforts for improving the neonatal health situation in Viet Nam.